2023
DOI: 10.33087/jiubj.v23i1.3180
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kontrol Diri dan Spiritualitas dengan Kenakalan Remaja di Kota Padang

Abstract: The number of juvenile delinquency continues to increase, it can be seen from the high number of brawls, drugs and illegal racing carried out by teenagers. Some of the influencing factors are self-control and spirituality. This study aims to determine whether there is a relationship between self-control and spirituality with juvenile delinquency. The research design used a cross sectional study method with a sample of 175 teenagers at Di Kota Padang, using a stratified random sampling technique. This research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Based on the Indonesian Child Protection Commission (KPAI) in 2018, there were 202 cases of student brawls in the city of Jakarta in the last 2 years where 74 used sharp weapons and 1 student died [7]. Another problem from the results of a study at the Blitar City Child Correctional Institution (LPKA) in 2018, it was found that out of 60 teenagers in LPKA, the 5 most types of delinquency were obtained, namely substance use (26.7%), robbery or theft (25 %), fights or brawls or acts of violence (20%), then sexual abuse (13.3%) and murder (13.3%) (Anjaswarni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Indonesian Child Protection Commission (KPAI) in 2018, there were 202 cases of student brawls in the city of Jakarta in the last 2 years where 74 used sharp weapons and 1 student died [7]. Another problem from the results of a study at the Blitar City Child Correctional Institution (LPKA) in 2018, it was found that out of 60 teenagers in LPKA, the 5 most types of delinquency were obtained, namely substance use (26.7%), robbery or theft (25 %), fights or brawls or acts of violence (20%), then sexual abuse (13.3%) and murder (13.3%) (Anjaswarni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%